5G Virtual Reality in the Design and Dissemination of Contemporary Urban Image System under the Background of Big Data. (14th February 2022) - Dong, Haoming; Liang, Xiaodan; Liu, Yalong; Wang, Dan
Abstract : As an important part of the soft power of urban culture, the importance of city image has received widespread attention from academic circles and society. The study of city image communication has become one of the important research directions in the field of communication in recent years. This research mainly discusses the application of 5G virtual reality in the design and dissemination of a contemporary urban image system under the background of big data. This research designs and develops a city image system that models and simulates virtual cities in a three-dimensional scene. The system consists of several different modules, including a data acquisition module, scene construction, and roaming module. The most important data resource formats used by this system are the DXF format and 3DS format, which can be created and acquired using digital stereo images in the data acquisition module. The data import and export module can convert the models in DXF format and 3DS format into Openfligt format models. The model editing and reconstruction module can visually edit and reconstruct the converted model, so that the space and attribute information of the recreated model is stored in the data storage and management system. Finally, a scene roaming module is created, and models are selected from the database to create a 3D city scene and provide interactive roaming information extraction. After the implementation of virtual reality technology, the per capita awareness of urban humanities reached 63.2%. The test results show that because the system integrates the respective advantages of the geographic information system, virtual reality, and database technology, it can better realize the modeling and simulation of digital cities under the conditions of three-dimensional visualization, which is conducive to the spread of urban image.